Biphasic Squamoid Alveolar Renal Cell Carcinoma: A Distinctive Subtype of Papillary Renal Cell Carcinoma?. (May 2016) - Hes, Ondrej; Condom Mundo, Enric; Peckova, Kvetoslava; Lopez, Jose I.; Martinek, Petr; Vanecek, Tomas; Falconieri, Giovanni; Agaimy, Abbas; Davidson, Whitney; Petersson, Fredrik; Bulimbasic, Stela; Damjanov, Ivan; et al.
Abstract : Biphasic squamoid alveolar renal cell carcinoma (BSARCC) has been recently described as a distinct neoplasm. Twenty-one cases from 12 institutions were analyzed using routine histology, immunohistochemistry, array comparative genomic hybridization (aCGH) and fluorescence in situ hybridization. Tumors were removed from 11 male and 10 female patients, whose age ranged from 53 to 79 years. The size of tumors ranged from 1.5 to 16 cm. Follow-up information was available for 14 patients (range, 1 to 96 mo), and metastatic spread was found in 5 cases. All tumors comprised 2 cell populations arranged in organoid structures: small, low-grade neoplastic cells with scant cytoplasm usually lining the inside of alveolar structures, and larger squamoid cells with more prominent cytoplasm and larger vesicular nuclei arranged in compact nests. In 9/21 tumors there was a visible transition from such solid and alveolar areas into papillary components. Areas composed of large squamoid cells comprised 10% to 80% of total tumor volume. Emperipolesis was present in all (21/21) tumors. Immunohistochemically, all cases were positive for cytokeratin 7, EMA, vimentin, and cyclin D1. aCGH (confirmed by fluorescence in situ hybridization) in 5 analyzable cases revealed multiple numerical chromosomal changes including gains of chromosomes 7 and 17 in all cases. These changes were further disclosed in 6 additional cases, which were unsuitable for aCGH. We conclude that tumors show a morphologic spectrum ranging from RCC with papillary architecture and large squamoid cells to fully developed BSARCC. Emperipolesis in squamoid cells was a constant finding. All BSARCCs expressed CK7, EMA, vimentin, and cyclin D1. Antibody to cyclin D1 showed a unique and previously not recognized pattern of immunohistochemical staining. Multiple chromosomal aberrations were identified in all analyzable cases including gains of chromosomes 7 and 17, indicating that they are akin to papillary RCC. Some BSARCCs were clinically aggressive, but their prognosis could not be predicted from currently available data. Present microscopic, immunohistochemical, and molecular genetic data strongly support the view that BSARCC is a distinctive and peculiar morphologic variant of papillary RCC.